Meningkatkan Kemampuan Membuat Manisan Pepaya Melalui Metode Proyek Bagi Anak Tunarungu - Agung Sumekar; Fatmawati Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2023)
This study aims to prove whether the project method can improve the possibility of making candied papaya for deaf children. The research method used is classroom action research, which consists of two cycles. The project method allows deaf students to properly and correctly make candied papaya. Based on the results of the study, the ability to make candied papaya increased initially compared to before using the project method. This is apparent from the research results that use the project method to improve the production of candied papaya.